Inovasi Pemasaran Industri Rumah Tangga Kerupuk Bawang Daliwangun Lamongan - Riwibowo, Nola; Wiratama, Dadang; Mashuri, Mashuri; Nurlaili, Rodhotul Evita; Wardhani, Erna Pramidya (Prima Abdika: Jurnal Pengabdian Masyarakat, 2025)
The onion cracker home industry founded by Mrs. Kusnawiyah in 1992 needs attention from the local village government. Even though it is able to survive amidst intense competition, the processed food and snack industry seems to be going nowhere. So far, this home industry only serves a limited number of orders. Marketing of onion crackers which only relies on word of mouth promotion and rudimentary packaging is felt to be less capable of reaching a wider range of consumers. The Daliwangun Village Government is collaborating with the Ahmad Dahlan Lamongan Institute of Technology and Business to develop the Onion Crackers Home Industry. This service begins with data collection carried out by interviews with related parties. The results of the interviews were used to find the right solution regarding the problems faced by the Daliwangun Onion Crackers Home Industry. Some of the activities carried out to increase the marketing of onion crackers are as follows: 1) Training on product sales strategies through online media, 2) Making more attractive packaging and 3) Using Facebook as an online promotional media. This activity was proven to be able to increase the sales volume of Daliwangun Onion Crackers.